PREMI ASURANSI JIWA GABUNGAN BERJANGKA DENGAN ASUMSI GOMPERTZ - Danu Aditya; Johannes Kho; T. P. Nababan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the annual premium of term insurance for joint life. In this kind of insurance, the sum assured of two people insured with the age of and is paid if only one of the insureds dies during the coverage period and then no more premium payment. The annual premium is affected by single premium and present value of annuity due, where Gompertz assumption is used in calculation. A bigger premium is obtained using the Gompertz assumption.